Control of gene expression in Helicobacter pylori using the Tet repressor - McClain, Mark S. (2013)
The lack of a versatile system to control gene expression in Helicobacter pylori has hampered efforts to study H. pylori physiology and pathogenesis. To overcome these limitations, we evaluated the utility of an inducible system based on the well-characterized Tet repressor (TetR) and Tet operator (tetO). As validation of this system, we introduced three copies of tetO into the promoter region upstream of the cagUT operon (encoding two virulence factors required for function of the H. pylori Cag type IV secretion system) and expressed tetR by introducing a codon-optimized gene into the chromosomal ureA locus. Introduction of the tetO copies upstream of cagUT did not disrupt promoter activity, as determined by immunoblotting for CagT. The subsequent introduction of tetR, however, did repress CagT synthesis. Production of CagT was restored when strains were cultured in the presence of the inducer, anhydrotetracycline. To demonstrate one potential application of this new tool, we analyzed the function of the Cag type IV secretion system. When the modified H. pylori strains were co-cultured with AGS cells, activity of the Cag type IV secretion system was dependent on the presence of anhydrotetracycline as evidenced by inducer-dependent induction of IL-8 secretion, CagA translocation, and appearance of type IV secretion system pili at the bacteria-host interface. These studies demonstrate the effectiveness of the tetR-tetO system to control gene expression in H. pylori and provide an improved system for studying H. pylori physiology and pathogenesis.